Sliding Mode Control Proposed Using a Clegg Integrator for Speed Control of a Three-Phase Induction Motor - Pablo Proaño; Renato Díaz; César Chillán; Jorge Medina; William Chamorro; José Zuñiga (Engineering Proceedings)
This work presents a new sliding mode control strategy that integrates a Clegg integrator into a Proportional Integral Derivative (PID) sliding surface to address controller saturation (windup) and chattering. The proposed controller was implemented on a Programmable Logic Controller (PLC) to regulate the speed of a three-phase induction motor using a frequency inverter as the final control element. Conventional PID and sliding mode controllers (SMCs) were also implemented for performance comparison. This study included tests for sudden set-point changes and disturbances to evaluate the control strategies. The proposed controller demonstrated a faster response compared to the PID control and a smoother control action compared to the SMC. The results and conclusions discuss the advantages and limitations of the proposed control strategy in comparison to the conventional methods.